Transnational management : text and cases in cross-border management - Bartlett, Christopher A., 1943- (Cambridge University Press, 2018)
Transnational Management provides an integrated conceptual framework to guide students and instructors through the challenges facing today's multinational enterprises. Through text narrative and cases, the authors skilfully examine the development of strategy, organizational capabilities, and management roles and responsibilities for operating in the global economy. The key concepts are developed in eight chapters that are supplemented by carefully selected practical case studies from world-leading case writers. All chapters have been revised and updated for this eighth edition to reflect the latest thinking in transnational management while retaining the book's strong integrated conceptual framework. Ten new cases have been added, and four others updated. A full range of online support materials are available, including detailed case teaching notes, almost 200 PowerPoint slides, and a test bank. Suitable for MBA, executive education and senior undergraduate students studying international management, international business or global strategy courses, Transnational Management offers a uniquely global perspective on the subject.